2005
DOI: 10.5713/ajas.2005.42
|View full text |Cite
|
Sign up to set email alerts
|

Can Moringa oleifera Be Used as a Protein Supplement for Ruminants?

Abstract: The possibility of using Moringa oleifera as a ruminant protein supplement was investigated by comparison between nutritive and anti-nutritive value of its different morphological parts with that of conventionally used Leucaena leucocephala leaf meal (LL). Parameters determined were chemical composition, rumen degradable protein (RDP), acid detergent insoluble protein (ADIP), pepsin soluble protein (PESP), non-protein nitrogen (NPN) total soluble protein (TSP) and protein potentially digested in the intestine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 15 publications
8
28
1
1
Order By: Relevance
“…The results also coincided with the finding of Ebenebe et al (2012) who reported chicks fed moringa based diets performed significantly (P<0.05) better than that of control group in term of higher weight gain and better feed conversion ratio. This improvement in body weight gain and feed conversion ratio may be attributed to rich content of nutrients in moringa (Sarwatt et al, 2004;Kakengi et al, 2003). Different levels of MLM exhibit significant influence on dressing percentage and breast meat of broilers (Table 2 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The results also coincided with the finding of Ebenebe et al (2012) who reported chicks fed moringa based diets performed significantly (P<0.05) better than that of control group in term of higher weight gain and better feed conversion ratio. This improvement in body weight gain and feed conversion ratio may be attributed to rich content of nutrients in moringa (Sarwatt et al, 2004;Kakengi et al, 2003). Different levels of MLM exhibit significant influence on dressing percentage and breast meat of broilers (Table 2 and Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The protein quality of MOL has been reported to be comparable to that of milk and eggs (Fahey 2005). Kakengi et al (2005) compared the nutritive values of different morphological components of MOL with Leucaena leucocephala leaf meal in Tanzania and they observed a high level of pepsin and total soluble protein in MOL. Previous study also showed that MOL contains high level of antioxidants such as flavonoids (Vongsak et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, Makkar and Becker (1997) indicated that, leaves of Moringa are very poor in anti-nutritional factors. Also, low feed consumption may be attributed to high crude fiber content in Moringa which may resulted in decreased palatability (Kakengi et al 2003).…”
Section: Results and Discussion Behavioral Observationmentioning
confidence: 99%